EXO [GLOBAL EYE(S)]: DYNAMIC RESPONSIVE SYSTEM CRITICAL REVIEW OF THE RESEARCH PROJECT, PROTOTYPE AND EXHIBITION CONCEPTS: Serbian - Ćirić, Dragana (Arhitektura i urbanizam, 2020)
The text aims to provide a critical review of the global eye(s) project’s development and results – its thematic, theoretical and scientific, methodological, strategic and organisational, design-interpretative and technical registers including spatial modes it uses and problematises regarding the architecture-machine concept. By following the process of transformation from the idea to the innovation strategy, research and innovation project, conceptual design, fabrication design, and finally test-model and prototype (analysing basic requirements for the technical solution and patent), while using the form of the exhibition design for the main experimental observation and assessment, it becomes possible to grasp all the challenges posed before the frameworks and standards of the architectural scientific and artistic approaches alongside those posed before the different interdisciplinary and cross-disciplinary theory-based and practice-based methodologies. Explanation of the complex network of narratives and procedures, methodologically guided towards the applicative solution, unfolds in parallel with the central architectural topic of dynamic responsive systems based on comprehensive sensing technologies and with the theme of the architectural operationalisations of the pervasive digital infrastructures, global monitoring and communication. The main contribution of the paper has been contained in its strategic proposal of the architectural design/engineering control and integration of different disciplinary competencies, processes and solutions (referring to robotics, mechanical, software and electronic design) towards the application in the spatial register (within the object, logic or a system). The architectural intelligent instrument/installation (architecture-instrument) has been presumed as the most appropriate spatial format that should have provided the proof of a technical concept for such an integrative architectural system. Therefore, it has been investigated towards a proper definition within the broader categories of a prototype and architecture-machine.